English Language Teaching Materials and Cross-Cultural Understanding: Are There Bridges or Divides? - Jayakaran Mukundan (TEFLIN Journal: A publication on the teaching and learning of English, 2005)
Abstract: English Language Teaching (ELT) materials can contribute immensely to cross-cultural understanding in the emerging globalised and borderless world. This is because there are common denominators present when materials are used in the teaching of the language across borders. An attempt to teach a language, for instance, must also consider the ways or the contexts in which it is used. Thus language cannot be detached from culture. The textbook or coursebook has been "standard equipment" for teachers for decades, maybe centuries. However the culture of the tar-get language has hardly ever been associated with the learning of the lanÂguage within textbooks. This paper discusses the importance in which the essential elements of language and communication and culture in text-books contribute towards language competency and cross-cultural under-standing. The writer also discusses the relevance and the importance of the awareness of the connections between language and cross-cultural unÂderstanding amongst curriculum developers and materials developers and users.